SAT0498 Abnormal electrocardiographic findings in a scandinavian cohort of patients with idiopathic inflammatory myopathies. (12th June 2018) - Korsholm, S.S.; Dastmalchi, M.; Diederichsen, A.C.; Andersson, D.C.; Lundberg, I.E.; Witting, N.; Krogager, M.E.; Friis, T.; Jacobsen, S.; Knudsen, J.B.; Diederichsen, L.P.
Abstract : Background: Idiopathic inflammatory myopathies (IIMs) are characterised by progressive muscle weakness and muscle fatigue. IIMs frequently appear with other organ involvement, e.g. the heart. Cardiac affection is often subclinical but associated with poor prognosis which makes early detection critical. Presence of autoantibodies is common in IIMs and autoantibodies are important biomarkers to confirm the diagnosis of IIMs. Autoantibodies may even predict organ involvement, e.g. the common myositis specific autoantibody anti-Jo1, which is a marker of lung involvement. So far, an autoantibody predicting cardiac involvement has yet to be identified. Objectives: The aim of this study was to identify and estimate presence of cardiac involvement detected by electrocardiography (ECG) and to evaluate possible associations between ECG changes and autoantibodies in a Scandinavian cohort of patients with IIMs. Methods: In a Scandinavian cross-sectional study, 241 patients with polymyositis (PM), dermatomyositis (DM), or inclusion body myositis (IBM) and 48 healthy controls (HCs) were investigated by ECG, basic cardiovascular assessments, and autoantibody profile including myositis specific autoantibodies (MSAs) and myositis associated autoantibodies (MAAs). Results: Compared to HCs, patients with IIMs more frequently had prolongation of QTc (p=0.037) and QRS (p=0.031). All patient groups had significantly longer QTc and QRS duration than HCs. In multivariate regression analysis of patients with IIMs, increased CRP (p=0.006) was associated to increased QTc. Pooled data for patients with IIMs and HCs showed an association between diagnosis of IIM and increased QTc duration (p<0.001). An association between presence of any MAA and QRS duration appeared in patients with IIMs (p=0.019). In pooled data for patients with IIMs and HCs, diagnosis of IIM was associated with QRS duration (p=0.001). Conclusions: Patients with IIMs, no matter of clinical subgroup, had a higher occurrence of cardiac abnormalities detected by ECG than HCs. Increased CRP and presence of any MAA were associated with increased QTc and QRS duration, respectively. These results support our notion of possible associations between inflammation and autoimmunity and cardiac affection in patients with IIMs. There is now a pressing need to set up a larger prospective study to validate the present findings. Disclosure of Interest: None declared